Self-Monitoring and Self-Esteem as Predictors of Academic Procrastination Among Postgraduate Students - Lasisi, Adekola Kamil; Salihu, Nurudeen Oganija (Institute For Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Academic procrastination is a common behavior among University students. This study examined self-monitoring and self-esteem as predictors of academic procrastination among The University of Ilorin Postgraduate Students. The research design for this study was a descriptive design of correlation type. The population for the study comprised 2,194 Postgraduate Students of the Institution (2021/2022) session. The sample used was 325 (178 male and 147 female) participants. The study utilized a research instrument and Self-Constructed Scales, specifically the Procrastination Assessment Scale Students, Self-Monitoring and Self-Esteem (PASSSMSEQ) for data collection. One research question and four research hypotheses guided the conduct of the study and the hypotheses were tested at a 0.05 level of significance using inferential statistics of P.P.M.C and Multiple Regression Analysis. The study found high academic procrastination among postgraduate students at the University of Ilorin with a significant relationship between self-monitoring and procrastination. Self-esteem also showed a significant relationship with procrastination. Both self-monitoring and self-esteem significantly contributed to the prediction of academic procrastination among these students. It was recommended, among others, that counseling psychologists should up their tactics in enabling a reduction in the academic procrastination of postgraduate students.